Cameroon : Fifth Review Under the Extended Credit Facility Arrangement and Request for a Waiver of Nonobservance of a Performance Criterion and Modification Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Cameroon. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Cameroon's Fifth Review Under the Extended Credit Facility Arrangement and Request for a Waiver of NonObservance of a Performance Criterion and Modification of Performance Criteria (PC). Growth reached 3.9 percent in the first half of 2019, supported by a rebound in the oil and gas sector. The overall fiscal deficit was 1.4 percent of GDP for the first three quarters of 2019, slightly better than the program's projection. External buffers are being rebuilt, despite external and domestic headwinds. The economy is coping with the impact of the suspension of production at the national oil refinery (SONARA). Program implementation over the first nine months of 2019 was mixed and faces challenges. The continuous PC on external arrears accumulation and three September ITs were also missed. Structural reforms are advancing but with delays. The IMF staff supports the authorities' requests for completion of the fifth review, a waiver of nonobservance of one continuous performance criterion and modification of one December 2019 and one 2020 performance criterion.